Checklist of herpetofauna in wetland ecosystems, Muara Angke Wildlife Reserve, Indonesia - Fania Dewi Nasihah; Mohamad Isnin Noer; Yusuf Muhammad (Bioma, 2025)
Urbanization causes damage to the natural environment and threatens conservation areas such as Muara Angke Wildlife Reserve. Urbanization has a negative impact on species diversity, including an increase in alien species, especially herpetofauna in Muara Angke Wildlife Reserve which acts as an indicator of environmental health. This study aims to record the presence of herpetofauna using Visual Encounter Survey (VES) and Acoustic Encounter Survey (AES) methods that can show significant changes in species presence over the past six years. The results showed that, of the 28 species previously identified, only 18 species were found in the most recent study. The number or diversity of herpetofauna species recorded can be affected by anthropogenic factors, such as housing, roads, and urban temperatures. Trails unaffected by human disturbance showed higher species diversity than affected trails such as the boardwalk. Paths with relatively undisturbed natural habitats recorded the highest diversity, while other paths such as the Angke river and embankment paths decreased.